Sharing risk with the government: How taxes affect corporate risk taking - LJUNGQVIST, Alexander (Institutional Knowledge at Singapore Management University, 2017)
Using 113 staggered changes in corporate income tax rates across U.S. states, we provide evidence on how taxes affect corporate risk-taking decisions. Higher taxes reduce expected profits more for risky projects than for safe ones, as the government shares in a firm's upside but not in its downside. Consistent with this prediction, we find that risk taking is sensitive to taxes, albeit asymmetrically: the average firm reduces risk in response to a tax increase (primarily by changing its operating cycle and reducing R&D risk) but does not respond to a tax cut. We trace the asymmetry back to constraints on risk taking imposed by creditors. Finally, tax loss-offset rules moderate firms’ sensitivity to taxes by allowing firms to partly share downside risk with the government.